CARMELINA: An important piece of the DPP-4 inhibitor CVOT puzzle. (July 2019) - Schernthaner, Guntram; Wanner, Christoph; Jurišić-Eržen, Dubravka; Guja, Cristian; Gumprecht, Janusz; Jarek-Martynowa, Iwona R.; Karasik, Avraham; Lalić, Nebojša; Mankovsky, Boris N.; Prázný, Martin; Tankova, Tsvetalina; Tsur, Anat; et al.
Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors are a class of glucose-lowering agent for type 2 diabetes (T2D) that are commonly used in clinical practice. With the recent disclosure of data from the CARMELINA cardiovascular outcomes trial (CVOT), which investigated linagliptin, CV and renal outcomes data are now available for four agents in the DPP-4 inhibitor class that are approved in most markets. To consider how the CARMELINA study may be interpreted, and the relevance for our clinical practice, we convened as an expert group of diabetes specialists from the Central and Eastern Europe region to discuss the new disclosures. Our discussions revealed a general confidence in safety across the class that is further supported by CARMELINA. However, we also concluded that there are important differences in the available evidence level between agents in the setting of heart failure and data on renal outcomes. Here, we noted the clinical relevance to our practice of the study population in CARMELINA, which is unique among CVOTs in including a majority of patients with chronic kidney disease (CKD). Given the risk for future development of renal impairment that is associated with T2D even in patients without current overt CKD, we believe that the CARMELINA study provides important new insights that are clinically relevant for a broad range of patients. Finally, we discuss how these insights can be integrated into the approach to the pharmacotherapeutic management of hyperglycaemia that is recommended in newly updated guidelines.